Early Childhood Moral Intelligence raised by Grandmother, Household Assistant, and Daycare Provider - Auliya, Falakhul; Sunarso, Ali; Pranoto, Yuli Kurniawati Sugiyo (Universitas Negeri Semarang, 2020)
Children do not only need intelligence in the academic field but also in interacting with others in accordance with the prevailing moral norms in society. Intelligence is influenced by parenting. In Indonesia, parenting of working parents’ families is usually carried out by grandmothers, household assistants, and daycare providers. This study aims to analyze differences in the moral intelligence of children raised by grandmothers, household assistants, and daycare providers. A total of 208 children aged 5-6 years (106 boys and 102 girls) in the city of Semarang, who were willing and approved by parents, were involved in this study. The children’s moral intelligence score in this study was obtained through storytelling test techniques presented by the researcher verbally, considering that early childhood children cannot read fluently. Data analysis techniques used descriptive analysis and one-way analysis of variance (ANOVA) with the help of SPSS 20.0 for Windows. The results of this study differed from previous studies in that there is no difference in the moral intelligence of children aged 5-6 years in the city of Semarang that is raised by grandmothers, household assistants, and daycare providers. Based on the results of the study it can be concluded that the roles of grandmothers, household assistants, and daycare providers are no different in fostering moral intelligence in early childhood. The level of moral intelligence of early childhood can also be influenced by the individual, age, social interaction, education, and the context of the situation. Discusses the moral intelligence of young children who are cared for by grandmothers, household assistants, and daycare providers